A scoping review of cost-effectiveness of screening and treatment for latent tuberculosis infection in migrants from high-incidence countries. Issue 1 (June 2015) - Zammarchi, Lorenzo; Casadei, Gianluigi; Strohmeyer, Marianne; Bartalesi, Filippo; Liendo, Carola; Matteelli, Alberto; Bonati, Maurizio; Gotuzzo, Eduardo; Bartoloni, Alessandro
Abstract Background In low-incidence countries, most tuberculosis (TB) cases occur among migrants and are caused by reactivation of latent tuberculosis infection (LTBI) acquired in the country of origin. Diagnosis and treatment of LTBI are rarely implemented to reduce the burden of TB in immigrants, partly because the cost-effectiveness profile of this intervention is uncertain. The objective of this research is to perform a review of the literature to assess the cost-effectiveness of LTBI diagnosis and treatment strategies in migrants. Methods Scoping review of economic evaluations on LTBI screening strategies for migrants was carried out in Medline. Results Nine studies met the inclusion criteria. LTBI screening was cost-effective according to seven studies. Findings of four studies support interferon gamma release assay as the most cost-effective test for LTBI screening in migrants. Two studies found that LTBI screening is cost-effective only if carried out in immigrants who are contacts of active TB cases. Discussion and Conclusions Our findings support the cost-effectiveness of LTBI diagnostic and treatment strategies in migrants especially if they are focused on young subjects from high incidence countries. These strategies could represent and adjunctive and synergistic tool to achieve the ambitious aim of TB elimination.